Outcomes in Patients With Hypertrophic Cardiomyopathy Awaiting Heart Transplantation. (March 2018) - Zuñiga Cisneros, Julio; Stehlik, Josef; Selzman, Craig H.; Drakos, Stavros G.; McKellar, Stephen H.; Wever-Pinzon, Omar
Abstract : Background: Current organ allocation policy and the rapid growth of mechanical support favor heart transplant (HT) candidates on left ventricular assist devices. HT candidates with hypertrophic cardiomyopathy (HCM) are usually not left ventricular assist device candidates and may have a disadvantage compared with dilated forms of cardiomyopathy. Methods and Results: Adult HT candidates registered in the Scientific Registry of Transplant Recipients database between 1999 and 2016 were included. HCM candidates were compared with ischemic cardiomyopathy (ICM) and non-ICM patients. Two eras were defined on the basis of the approval date of the first continuous-flow left ventricular assist device for bridge-to-transplant in the United States (2008). Patients outcomes were evaluated while on the waitlist and after HT. The proportion of patients with HCM listed for HT increased by 44% in era 2 compared with era 1. Waitlist mortality in patients with ICM (15.5%–8.7%) and non-ICM (14.2%–8.2%) declined across eras, but minimal decline was observed in HCM patients (11.7%–9.6%; P =0.06). In era 2, the 12-month rate of HT in HCM (64.8%) was comparable to that of ICM (60.9%) and non-ICM (62.7%) patients ( P =0.06). Post-transplant survival in HCM patients was the most favorable in the most recent era (1 year: 91.6% and 5 years: 82.5%; P <0.05 for all comparisons). Conclusions: The number of patients with HCM in need of HT is increasing. Although post-transplant survival in HCM is excellent, waitlist mortality is substantial and with minimal decline in the most recent era, despite the frequent use of listing status upgrade by exception in this patient cohort. Different strategies to improve the performance of the organ allocation system in patients with HCM are needed. Abstract : Supplemental Digital Content is available in the text.